PEMBATASAN LIVE STREAMING DI MEDIA SOSIAL PADA AKSI DEMONSTRASI: TINJAUAN HUKUM PENYIARAN DAN HAK ATAS INFORMASI DI INDONESIA - Putri Madaniah; Safinaturahmah; Suparmin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines restrictions on live streaming features on social media in the context of demonstrations, from the perspective of broadcasting law and the right to information in Indonesia. This study stems from the increasing use of live streaming as a means of conveying public information in real time, which on the one hand strengthens transparency, but on the other hand has the potential to spread provocative content and disrupt public order. This study uses a normative juridical approach with a literature review method on broadcasting regulations, human rights, and digital restriction practices. The results of the study show that live streaming restrictions can be justified under broadcasting law based on Law No. 32 of 2002, and are valid according to human rights principles as long as they are carried out in accordance with the law and for legitimate purposes. This conclusion reinforces the importance of balancing the protection of public order and the fulfillment of the right to public information. The implication of this study is the need for fair, transparent, and deliberative democracy-based regulations in governing digital broadcasting in the era of social media.